2022
DOI: 10.1002/advs.202105299
|View full text |Cite
|
Sign up to set email alerts
|

Strain Adjustment Realizes the Photocatalytic Overall Water Splitting on Tetragonal Zircon BiVO4

Abstract: Overall water splitting to generate H 2 and O 2 is vital in solving energy problem. It is still a great challenge to seek efficient visible light photocatalyst to realize overall water splitting. In this work, the tetragonal zircon BiVO 4 is prepared by epitaxial growth on FTO substrate and its overall water splitting reaction is studied. Under the influence of epitaxial strain, the conduction band position shifts negatively and beyond H + /H 2 reduction potential (0 V vs NHE), which enables it to possess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Nevertheless, owing to the complex electron transfer steps and high energy barrier. The poor H2 evolution performance and apparent quantum efficiency (AQE) lead to hard implications of photocatalytic OWS (Table 1) [118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] .…”
Section: Design and Modification Strategies Of Photocatalytic Overall...mentioning
confidence: 99%
“…Nevertheless, owing to the complex electron transfer steps and high energy barrier. The poor H2 evolution performance and apparent quantum efficiency (AQE) lead to hard implications of photocatalytic OWS (Table 1) [118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] .…”
Section: Design and Modification Strategies Of Photocatalytic Overall...mentioning
confidence: 99%
“…Bismuth vanadate (BiVO 4 ), as the most promising PEC water oxidation photoanode material, has been attracting researchers’ attention in recent years. It possesses a narrow band gap that allows it to absorb more visible light. In addition, the valence band position and the conduction band position of BiVO 4 photoanode are, respectively, close to 2.5 and 0 V versus reversible hydrogen electrode (RHE) due to the empty Bi 6p track that overlaps the back-key V 3d-O 2p track, which has strong catalytic capacity of oxygen production (Figure a) .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] However, the practical utilization of electrocatalytic water splitting to generate hydrogen is limited by the intrinsically sluggish kinetics of the anodic oxygen evolution reaction (OER, 4OH À / O 2 + 2H 2 O + 4e À , 1.23 V vs. RHE) involving multi-step proton-coupled electronic processes. 18,[20][21][22][23] Hence, the development and design of new electrocatalysts for both cathode and anode reactions has become a research hotspot. 24 Recently, it has been demonstrated that the oxidation of thermodynamically favorable organic small molecules, such as urea, [25][26][27] hydrazine, [28][29][30] ethanol, 31,32 and 5-hydroxymethylfurfural, 33,34 instead of the oxygen evolution reaction, can effectively improve the anode reaction efficiency and achieve hydrogen production at a lower voltage.…”
Section: Introductionmentioning
confidence: 99%
“…14–19 However, the practical utilization of electrocatalytic water splitting to generate hydrogen is limited by the intrinsically sluggish kinetics of the anodic oxygen evolution reaction (OER, 4OH − → O 2 + 2H 2 O + 4e − , 1.23 V vs. RHE) involving multi-step proton-coupled electronic processes. 18,20–23 Hence, the development and design of new electrocatalysts for both cathode and anode reactions has become a research hotspot. 24…”
Section: Introductionmentioning
confidence: 99%